2019
DOI: 10.1111/bcp.13855
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, pharmacokinetics and effect on serum uric acid of the myeloperoxidase inhibitor AZD4831 in a randomized, placebo‐controlled, phase I study in healthy volunteers

Abstract: Aims Myeloperoxidase activity can contribute to impaired vascular endothelial function and fibrosis in chronic inflammation‐related cardiovascular disease. Here, we investigated the safety, tolerability and pharmacokinetics of the myeloperoxidase inhibitor, AZD4831. Methods In this randomized, single‐blind, placebo‐controlled, phase I, first‐in‐human study, healthy men in five sequential cohorts were randomized 3:1 to receive a single oral dose of AZD4831 (5, 15, 45, 135 or 405 mg) or placebo, after overnight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…The starting dose of 5 mg in cohort 1 was the same starting dose as previously evaluated in a SAD study and, although some accumulation was predicted following once‐daily dosing to steady‐state, exposures were predicted to be well below the highest doses/exposures explored in that study 10 . A period of 10 days was deemed sufficient to reach steady‐state conditions given the half‐life of AZD4831 as determined in the SAD study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The starting dose of 5 mg in cohort 1 was the same starting dose as previously evaluated in a SAD study and, although some accumulation was predicted following once‐daily dosing to steady‐state, exposures were predicted to be well below the highest doses/exposures explored in that study 10 . A period of 10 days was deemed sufficient to reach steady‐state conditions given the half‐life of AZD4831 as determined in the SAD study.…”
Section: Methodsmentioning
confidence: 99%
“…Samples for determination of AZD4831 in urine were analyzed by Covance Laboratories Ltd. AZD4831 and the stable labeled internal standard [ 13 C 3 15 N 2 ]AZD4831 were prepared from urine by sample dilution and analyzed by liquid chromatography tandem mass spectrometry. This method was validated prior to sample analysis in the range 20–20,000 nM in urine, using a 25 µL sample aliquot 10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AZD4831 was shown to be well tolerated: no adverse effects have been observed except maculopapular rash but only at high doses (135 mg) and in 33% of the participants [77].…”
Section: Thioxanthine Derivativesmentioning
confidence: 93%
“…A high-fat and high-calorie meal led to a reduced absorption rate by 44% compared to the administration without food intake. It has been found also that AZD4831 has a long plasma half-life (t 1/2 = 38-50 h) and the main clearance route is renal [77]. In vitro metabolism studies have indicated that the cytochrome P450 (CYP) enzymes CYP3A4 and CYP3A5 are involved in the metabolism of AZD4831 [77].…”
Section: Thioxanthine Derivativesmentioning
confidence: 99%